Resolving conflicts using appropriate communication channel in project execution: An assessment of the Tema motorway expansion project - Afanyedor, Nutifafa (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements of the Awarded Degree of Master of Science in Project Management.